Promoting Multilingual Communicative Competence for the Labor Market - Alaoui, Sadik Madani (European Scientific Journal, ESJ, 2017)
Over the past decades, globalization has been completely changing the context of the labor market such that the importance of learning languages as a means of cultural understanding cannot be ignored. As a result, employers look for people who have experience from different countries and have shown that they are able to adapt to different languages and cultures. The issue of learning languages and developing intercultural competence stands at the heart of human experience, reflecting not only cultures but also providing a key to better understanding them. The paper supports the promotion of a dialogue among various partners, educators and decision-makers as a good way to respond to the challenges associated with the development of language skills for the job market. Seen from an employment perspective, promoting multilingual communicative competence for the labor market is currently regarded as a means to an end. This paper examines ways to sharpen the focus on employability promotion in the Moroccan ENSAM School of Engineering. Moroccan would-be engineers will be shown to increase their chances of finding jobs, not only nationally but also internationally through greater multilingual competence.